Dukungan Keluarga Dalam Merawat Anak Dengan Thalassemia Beta Mayor - Rezka Nurvinanda; Sri Mulatsih; Sri Hartini; Intansari Nurjannah (STIKES Citra Delima Bangka Belitung, 2019)
Family Support In Caring For Children With Thalassemia Beta Major ABSTRACT Background: Thalassemia is hemolytic anemia diseases and genetically inherited. Prevalence of Thalassemia’s gen carrier on indonesian population amounts 3-8%. Children with beta major thalassemia has to receive long term treatment so potentially providing impact for children and their family. Study aims to describes family experiences during taking care the children with beta thalassemia major. Method: This study used phenomenology approach and data collected by indepth interview of 8 participants who were mothers as the primary caregiver in caring for children with beta thalassemia major. Data analysis using Colaizzi method. Result: There were seven themes found related to family experiences in caring for children with thalassemia included family ability to caring children; negative response from family; challenge on caring children; barriers during taking care children; supporting sources for family; family effort to faced stressor; and influencing factors on coping strategies. Conclusion: The source of support for the family while caring for children with major beta thalassemia is obtained, both from internal and external support in the form of instrumental, emotional, information and financial support. Keyword: Family Support, Children, Thalassemia